Taxonomic and Functional Fecal Microbiota Signatures Associated With Insulin Resistance in Non-Diabetic Subjects With Overweight/Obesity Within the Frame of the PREDIMED-Plus Study - Atzeni, Alessandro; Bastiaanssen, Thomaz F. S.; Cryan, John F.; Tinahones, Francisco J.; Vioque, Jesús; Corella, Dolores; Fitó, Montserrat; Vidal, Josep; Moreno-Indias, Isabel; Gómez-Pérez, Ana M.; Torres-Collado, Laura; Coltell, Oscar; et al. (Frontiers in Endocrinology, 2022)
Objective: An altered gut microbiota has been associated with insulin resistance (IR), a metabolic dysfunction consisting of cellular insulin signaling impairment. The aim of the present study is to determine the taxonomic and functional fecal microbiota signatures associated with HOMA-IR index in a population at high cardiovascular risk. Methods: A total of 279 non-diabetic individuals (55-75 years aged) with overweight/obesity and metabolic syndrome were stratified according to tertiles of HOMA-IR index. Blood biochemical parameters, anthropometric measurements and fecal samples were collected at baseline. Fecal microbial DNA extraction, 16S amplicon sequencing and bioinformatics analysis was performed. Results: Desulfovibrio, Odoribacter and Oscillospiraceae UCG-002 were negatively associated with HOMA-IR, whereas predicted total metagenome analysis revealed metabolic modules mainly linked to amino acid degradation. Butyricicoccus, Erysipelotrichaceae UCG-003, Faecalibacterium were positively associated with HOMA-IR, whereas predicted total metagenome analysis revealed metabolic modules mainly linked to saccharide degradation. These bacteria contribute differentially to the metabolic modules, being the degree of contribution dependent on IR. Both taxa and metabolic modules negatively associated to IR are linked to mechanisms involving sulfate reducing bacteria, improvement of intestinal gluconeogenesis and production of acetate. Furthermore, both taxa and metabolic modules positively associated to IR were linked to production and mechanisms of action of Butyrate. Conclusions: Specific taxonomic and functional fecal microbiota signatures associated with IR were identified in a population of overweight/obese individuals at high cardiovascular risk. These findings suggest that targeting specific taxa could be a potential strategy to improve IR.